Molybdenum-based negative electrode material and preparation method and application thereof
By using nitrogen and sulfur-cooped carbon nanoshort rods in the molybdenum-based anode material to fill the core-shell MoO2-MoS2 nanoroller, the problem of poor circulation performance of MoO2-MoS2 materials in the prior art is solved, and efficient Preparation of sodium/lithium-ion battery negative electrode material, with excellent rate performance and cycle stability.
Patent Information
- Application Number
- CN202411464321.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The MoO2 material prepared in the prior art with a MoS2 layer covered with a MoS2 layer has poor long-term circulation performance when used as the negative electrode of a sodium/lithium ion battery.
A carbon nanorod co-doped short rod with nitrogen and sulfur is used as a carrier to fill the core-shell MoO2-MoS2 nanoroller, and a MoO2-MoS2 core-shell structure is formed by domain-limited pyrolysis treatment, simplifying the preparation process and improving material performance.
The excellent rate performance and high cycle stability of molybdenum-based anode material in sodium/lithium-ion batteries are achieved, avoiding the complexity and insufficient performance of additional sulfur sources.
Smart Images

Figure CN119400816A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of negative electrode materials for sodium / lithium ion batteries, and in particular relates to a molybdenum-based negative electrode material and a preparation method and application thereof. Background Art
[0002] Negative electrode materials play a vital role in the energy density and cycle life of batteries. Molybdenum disulfide (MoS2) has become a promising negative electrode material in sodium / lithium ion batteries due to its low cost, large interlayer spacing (~0.62nm), significant pseudocapacitive properties, and theoretical capacity of up to 670mAh / g. However, MoS2 faces many challenges in practical applications, including inherent poor conductivity, slow electrochemical reaction kinetics, large volume changes during charge and discharge cycles, and even structural pulverization, which severely limits its rate performance and cycle stability in sodium / lithium ion batteries.
[0003] Constructing heterostructures is an effective way to overcome the above challenges. By coupling electrode materials with different band gaps to form a stable nanostructure, a built-in electric field is created at the heterojunction, which not only reduces the ion diffusion energy barrier but also significantly promotes the redox reaction (Small 2023, 19, 2207919; J. Energy Chem. 2023, 82, 268). Yang et al. found that in Fe 1-x The S / MoS2 heterostructure interface forms an "ion reservoir" that greatly reduces the Na + The diffusion barrier of Na-ion batteries is reduced, thus enhancing the rate performance of Na-ion batteries (Nano-MicroLett. 2019, 11: 80). However, due to the lattice mismatch of different components, the construction of MoS2-based heterostructures is still very challenging. Monoclinic molybdenum dioxide (MoO2) with tunnel structure has high conductivity (~1.1×10 4 S / cm), which is beneficial to promote charge transfer during electrochemical reactions (Energy Storage Mater. 2018, 11, 161). At the same time, it has a theoretical capacity of up to 836 mAh / g, as well as pseudocapacitive properties similar to MoS2 (Adv. Energy Mater. 2017, 7, 1602880). These advantages undoubtedly make MoO2 an ideal choice for integration with MoS2 to construct a unique molybdenum-based heterostructure negative electrode material. The prior art mainly prepares MoO2 materials covered with a MoS2 layer on the surface by sulfurization and roasting by adding additional sulfur powder or the like as a sulfur source (J. Phys. Chem. C 2014, 118, 18387; Part. Part. Syst. Charact. 2017, 341600223), but the material has poor long-term cycle performance when used as a negative electrode for sodium / lithium ion batteries. Summary of the invention
[0004] The present invention provides a molybdenum-based negative electrode material and a preparation method and application thereof, which solve the problem that the MoO2 material with a surface covered with a MoS2 layer prepared in the prior art has poor long-term cycle performance when used as a negative electrode of a sodium / lithium ion battery.
[0005] A first aspect of the present invention provides a molybdenum-based negative electrode material, comprising nitrogen- and sulfur-co-doped carbon nanorods, wherein the carbon nanorods are filled with core-shell molybdenum-based nanoscrolls;
[0006] The core-shell molybdenum-based nanoscroll comprises a molybdenum dioxide core and a molybdenum disulfide shell layer with a curved structure, and the number of layers of the molybdenum disulfide is 12 to 35.
[0007] The MoO2 in the molybdenum-based negative electrode material is a monoclinic phase, and the MoS2 is a 2H phase. Both are derived from the MoO3 nanorod template in the precursor, forming a large number of heterogeneous interfaces; the MoS2 shell has a curved structural feature, and the number of layers can be adjusted. Too many MoS2 shell layers are not conducive to the diffusion of sodium / lithium ions into the molybdenum dioxide core, and too few layers cannot maintain a stable core-shell structure during the charge and discharge process.
[0008] The second aspect of the present invention provides a method for preparing the molybdenum-based negative electrode material. The reaction formula involved in the formation process is: 2MoO3+C=2MoO2+CO2↑; 2MoO2+15C+6(NH4)2S2O8=2MoS2+12NH3↑+8SO2↑+15CO2↑+6H2O↑. The preparation method is:
[0009] The MoO3 nanorods are ultrasonically dispersed in deionized water, and a nitrogen-containing organic carbon source monomer solution is injected under ice bath and continuous stirring conditions, and then a sulfur-containing initiator solution with strong oxidizing properties treated in an ice bath is added dropwise to initiate a polymerization reaction of the nitrogen-containing organic carbon source, and the reaction mixture is directly transferred to an evaporating dish, and after drying, a molybdenum trioxide-organic polymer precursor in which the sulfur-containing initiator is uniformly dispersed is obtained;
[0010] The molybdenum trioxide-organic polymer precursor in which the sulfur-containing initiator is uniformly dispersed is placed in a quartz boat, loaded into a programmed temperature tube furnace, and inert gas protection is introduced. A confined pyrolysis treatment is performed at 600-800° C. to make the sulfur-containing initiator in situ sulfurize the molybdenum trioxide-organic polymer precursor, and the molybdenum-based negative electrode material is obtained by cooling with the furnace; wherein the molar ratio of the molybdenum trioxide nanorods, the nitrogen-containing organic carbon source monomer and the sulfur-containing initiator is 1.0:5-15:1.0.
[0011] Preferably, during the confined pyrolysis, the temperature is first raised from room temperature to 300°C at a rate of 1°C / min for 3 hours to remove the adsorbed water in the precursor and convert the organic polymer into amorphous carbon; then the temperature is further raised to 600-800°C at a rate of 2-10°C / min for 2-5 hours. During the second heating process, if the heating rate is too slow, the sulfur-containing initiator will be decomposed too much, and if it is too fast, the sulfur-containing initiator will be insufficiently decomposed, both of which are not conducive to the sulfurization of the precursor.
[0012] The present invention does not add an additional sulfur source during the confined pyrolysis, but directly uses the sulfur-containing initiator that has been uniformly dispersed in the molybdenum trioxide-organic polymer precursor in the previous step to achieve in-situ sulfurization of the molybdenum trioxide-organic polymer precursor.
[0013] Preferably, the sulfur-containing initiator is ammonium persulfate.
[0014] Preferably, when preparing the sulfur-containing initiator dispersed molybdenum trioxide-organic polymer precursor, the ammonium persulfate is first prepared into a solution and then the reaction is initiated; wherein the concentration of the ammonium persulfate solution is 1.0 to 3.0 mol / L.
[0015] Preferably, the nitrogen-containing organic carbon source monomer is one or more of pyrrole, aniline, and dopamine hydrochloride.
[0016] Preferably, the preparation method of the molybdenum trioxide nanorods is:
[0017] Molybdate and ferric chloride hexahydrate are added into a dilute nitric acid solution and subjected to a constant temperature hydrothermal reaction to obtain molybdenum trioxide nanorods.
[0018] Preferably, the molar ratio of the molybdenum in the molybdate, the iron in the ferric chloride hexahydrate, and the dilute nitric acid is 0.5-4.0:0.01-0.05:1.0-5.0.
[0019] Preferably, the isothermal hydrothermal reaction is carried out at 150-220° C. for 15-25 hours.
[0020] The third aspect of the present invention protects the use of the molybdenum-based negative electrode material in the negative electrode of a sodium-lithium ion battery or a lithium ion battery.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The molybdenum-based negative electrode material provided by the present invention is a core-shell MoO2-MoS2 nanoscroll composite material filled with carbon nanorods; the MoO2-MoS2 nanoscroll is obtained by homologous transformation of MoO3 nanorods, and has a unique core-shell structural feature. The two form a large number of heterogeneous interfaces, providing abundant reaction active sites for storing sodium ions or lithium ions and accelerating the electrochemical reaction kinetics; the MoS2 shell has a curved structural feature, and the number of MoS2 layers is regulated at 12 to 35 layers by limiting the pyrolysis temperature and the amount of sulfur-containing initiator, so as to obtain excellent sodium / lithium storage performance, and has excellent rate performance and cycle stability when used in sodium / lithium batteries.
[0023] 2. The preparation method of the molybdenum-based negative electrode material provided by the present invention uses MoO3 nanorods as templates, and coordinates and polymerizes nitrogen-containing organic carbon source monomers on the surface thereof, and after drying, obtains a molybdenum trioxide-organic polymer precursor in which a sulfur-containing initiator is uniformly dispersed, and then performs confined pyrolysis under high temperature conditions to reduce MoO3 to MoO2, and then controllably vulcanizes the sulfur-containing initiator through decomposition to form a curved MoS2 coating layer in situ on the surface of the highly conductive MoO2. This method is simple and efficient, and MoO2 and MoS2 are obtained by in-situ conversion of MoO3, which is very beneficial for constructing a large number of heterogeneous interfaces.
[0024] 3. The present invention directly utilizes the sulfur-containing initiator in the polymerization reaction process as the sulfur source, without the need to add an additional sulfur source, thereby preventing the additionally added sulfur source from being unable to form core-shell MoO2-MoS2 nanoscrolls, and avoiding the complicated separation and purification process after the polymerization reaction is completed; the sulfur-containing initiator is uniformly dispersed in the molybdenum-based precursor, which is conducive to in-situ sulfurization to form a core-shell structure; the sulfur-containing initiator with strong oxidizing properties partially etches the carbon layer during the pyrolysis process to form a higher porosity, which is conducive to the rapid penetration of the electrolyte in the electrochemical process.
[0025] 4. The molybdenum-based negative electrode material provided by the present invention has high specific capacity, high rate performance and high cycle stability when applied to the negative electrode of sodium ion batteries and lithium ion batteries, showing broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Transmission electron microscopy images of the molybdenum-based negative electrode material prepared in Example 1 at different magnifications: a) 50nm, b) 10nm; and the magnified image of the corresponding core and shell regions of the nanoscroll c) and the Fourier transform image d);
[0027] Figure 2 Scanning electron microscope images of the molybdenum-based negative electrode material prepared in Example 1 at different magnifications: a) 1 μm, b) 200 nm;
[0028] Figure 3This is a diagram showing the element surface distribution results of the molybdenum-based negative electrode material prepared in Example 1;
[0029] Figure 4 X-ray diffraction patterns of the platinum-based negative electrode materials prepared in Example 1: a), Comparative Example 1: b), Comparative Example 2: c) and Comparative Example 3: d);
[0030] Figure 5 Transmission electron microscopy image of the molybdenum-based negative electrode material prepared in Comparative Example 1: a) and selected area electron diffraction image: b);
[0031] Figure 6 Scanning electron microscope images of the molybdenum-based negative electrode material prepared in Comparative Example 2 at different magnifications: a) 1 μm, b) 200 nm;
[0032] Figure 7 Transmission electron microscopy images of the molybdenum-based negative electrode material prepared in Comparative Example 2 at different magnifications: a) 50nm, b) 5nm;
[0033] Figure 8 Scanning electron microscope images of the molybdenum-based negative electrode material prepared in Comparative Example 3 at different magnifications: a) 1 μm, b) 200 nm;
[0034] Fig. 9 Transmission electron microscopy images of the molybdenum-based negative electrode material prepared in Comparative Example 3 at different magnifications: a) 50nm, b) 5nm;
[0035] Fig.10 The first, second and third cycle constant current charge and discharge performance curves of the molybdenum-based negative electrode materials prepared in Example 1: a) and Comparative Example 1: b) when used in sodium ion batteries;
[0036] Fig.11 The rate performance diagram of the molybdenum-based negative electrode materials prepared in Example 1: a), Comparative Example 1: b), Comparative Example 2: c) and Comparative Example 3: d) when used in sodium ion batteries;
[0037] Fig.12 The cycle stability performance of the molybdenum-based negative electrode materials prepared in Example 1: a) and Comparative Example 1: b) when used in sodium ion batteries at a current density of 0.1 A / g;
[0038] Fig.13 Cyclic stability performance of the molybdenum-based negative electrode materials prepared in Example 1: a) and Comparative Example 1: b) when used in sodium ion batteries under a current density of 1.0 A / g;
[0039] Fig.14 The cycle stability performance of the molybdenum-based negative electrode material prepared in Example 1 when used in a sodium ion battery at a current density of 5.0 A / g;
[0040] Fig.15 The first, second and third cycle constant current charge and discharge performance curves of the molybdenum-based negative electrode material prepared in Example 1 when used in a lithium-ion battery: a) and rate performance diagram: b);
[0041] Fig.16 The molybdenum-based negative electrode material prepared in Example 1 has a cycle stability performance at a current density of 0.2 A / g when used in a lithium-ion battery. DETAILED DESCRIPTION
[0042] The technical solutions in the present invention will be described clearly and completely below in conjunction with the specific implementation of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] The methods described in the embodiments of the present invention are conventional methods unless otherwise specified. The materials, reagents, etc. used can be obtained from commercial sources unless otherwise specified.
[0044] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. Among them, A and B can be singular or plural; the single symbol " / " means "or".
[0045] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of A, B or C", or "at least one of A, B and C" can represent any one of A, B, C, or A+B, or A+C, or B+C, or A+B+C, where A, B, C can be single or multiple, respectively.
[0046] In the following description of this embodiment, the order of serial numbers does not mean the order of execution. Some or all of the steps can be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of this embodiment.
[0047] In the following description of the present embodiment, the numerical range should be understood to also specifically disclose each intermediate value between the upper and lower limits of the range. Any stated value or intermediate value in the stated range and any other stated value or each smaller range between the intermediate values in the stated range are also included in the present embodiment, and the upper and lower limits of the smaller range can be independently included or excluded in the range.
[0048] Unless otherwise stated, the technical / scientific terms used in the present embodiment have the same meanings as those generally understood by those skilled in the art to which the present application belongs. Although the present application only describes preferred methods and materials, any similar or equivalent methods and materials may also be used in the implementation or testing of the present application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of any conflict with any incorporated document, the content of this specification shall prevail.
[0049] The present invention provides a molybdenum-based negative electrode material and a preparation method and application thereof, which mainly uses MoO3 nanorods as templates, coordinates and polymerizes nitrogen-containing organic carbon source monomers on the surface, and obtains a molybdenum trioxide-organic polymer precursor uniformly dispersed with a sulfur-containing initiator after drying; then, confined pyrolysis is performed under high temperature conditions to reduce MoO3 to MoO2, and controllable sulfurization is further achieved through the decomposition of the sulfur-containing initiator, and a curved MoS2 coating layer is in situ constructed on the surface of the highly conductive MoO2. The prepared molybdenum-based negative electrode material is used as a negative electrode material for sodium / lithium ion batteries.
[0050] The preparation method comprises the following steps:
[0051] Molybdate and ferric chloride hexahydrate are added to a continuously stirred dilute nitric acid solution in sequence, and a clear and transparent mixed solution is obtained after complete dissolution. The mixed solution is then transferred to a polytetrafluoroethylene-lined reactor, and MoO3 nanorods are collected after a constant temperature hydrothermal reaction and purification treatment.
[0052] The MoO3 nanorods are ultrasonically dispersed in deionized water, and a nitrogen-containing organic carbon source monomer solution is injected under ice bath and continuous stirring conditions. Then, an ice bath-treated sulfur-containing initiator is added dropwise to initiate a polymerization reaction of the carbon source monomer. The reaction mixture is directly transferred to an evaporating dish and dried to obtain a molybdenum trioxide-organic polymer precursor in which the sulfur-containing initiator is uniformly dispersed.
[0053] The molybdenum trioxide-organic polymer precursor is placed in a quartz boat, loaded into a programmed temperature tubular furnace, and protected by inert gas. A confined pyrolysis treatment is performed under high temperature conditions to allow the sulfur-containing initiator to in-situ sulfurize the molybdenum-based precursor. The furnace is cooled to obtain a nitrogen and sulfur co-doped carbon-coated MoO2-MoS2 core-shell structure material.
[0054] In a specific embodiment, the molybdate is one or more of ammonium molybdate tetrahydrate, sodium molybdate dihydrate, and potassium molybdate, and the concentration of the formed molybdate solution is 0.05-0.40 mol / L; the concentration of the dilute nitric acid solution is 0.10-0.50 mol / L; the concentration of the ferric chloride hexahydrate solution is 0.001-0.005 mol / L; the nitrogen-containing organic carbon source monomer is one or more of pyrrole, aniline, and dopamine hydrochloride, and the molar ratio of the nitrogen-containing organic carbon source monomer to the molybdenum trioxide template is (5-15):1; the concentration of the sulfur-containing initiator is 1.0-3.0 mol / L; the temperature of the high-temperature pyrolysis is 600-800°C, and the reaction time is 2-5h.
[0055] The abbreviations of some raw materials in the examples of the present invention are:
[0056] Polyvinylidene fluoride: PVDF, N-methyl-2-pyrrolidone: NMP; Polypropylene: PP.
[0057] The specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0058] Example 1
[0059] A method for preparing a molybdenum-based negative electrode material:
[0060] 0.618 g of ammonium molybdate tetrahydrate (Mo content is 3.5 mmol) and 0.014 g of ferric chloride hexahydrate (Fe content is 0.005 mmol) were weighed and added in sequence to 20 mL of a continuously stirred 0.25 mol / L dilute nitric acid solution. A clear and transparent mixed solution was obtained after complete dissolution. The solution was then transferred to a 40 mL polytetrafluoroethylene-lined reactor and placed in a 200 °C oven for constant temperature reaction for 20 hours. After the hydrothermal reaction was completed, the MoO3 nanorods were separated by centrifugation, washed with water and ethanol in sequence for purification, and collected after drying.
[0061] 0.144 g MoO3 nanorods (1.0 mmol) were ultrasonically dispersed in 40 mL deionized water. Under ice bath and continuous stirring conditions, 675 μL pyrrole monomer solution (10.0 mmol) was injected. Then 10 mL of 1.0 mol / L ice-bath treated ammonium persulfate solution (S content was 10.0 mmol) was added dropwise to initiate the polymerization reaction of the pyrrole monomer. It was observed that the mixed solution quickly changed from white to black. The ice bath and stirring reaction were continued for 5 hours. The reaction mixture was directly transferred to an evaporating dish. After sufficient drying, a molybdenum trioxide-polypyrrole precursor uniformly dispersed in ammonium persulfate was obtained.
[0062] The molybdenum trioxide-polypyrrole precursor is placed in a quartz boat and loaded into a programmed temperature tubular furnace. Argon gas is introduced for protection at a flow rate of 30 mL / min. The temperature is first increased from room temperature to 300°C at a rate of 1°C / min and maintained for 3 hours. Then the temperature is further increased to 700°C at a rate of 10°C / min and maintained for 2 hours for confined pyrolysis treatment, so that ammonium persulfate in situ sulfurizes the molybdenum trioxide-polypyrrole precursor. After the furnace body is naturally cooled to room temperature, the molybdenum-based negative electrode material, i.e., nitrogen and sulfur co-doped carbon nanorods (named MoO2@MoS2@C) is obtained.
[0063] Figure 1 Transmission electron microscopy images of the molybdenum-based negative electrode material prepared in Example 1 at different magnifications: a) 50nm, b) 10nm; and the magnified image of the corresponding core and shell regions of the nanoscroll c) and the Fourier transform image (d). Figure 1 As shown, a large number of core-shell MoO2-MoS2 nanoscrolls with a size of about 20-50nm are formed in the prepared MoO2@MoS2@C material, and the MoO2 and MoS2 are in close contact to produce rich heterogeneous interfaces; the inner core MoO2 has a very high crystallinity, and clear lattice stripes of (100) and (220) crystal planes can be observed; the shell MoS2 has a curved structural feature, with about 15 layers, and clear (002) interlayer spacing lattice stripes can be observed, and the corresponding interlayer spacing is 0.641nm, which is larger than the theoretical value of 0.620nm.
[0064] Figure 2 Scanning electron microscope images of the molybdenum-based negative electrode material prepared in Example 1 at different magnifications: a) 1 μm, b) 200 nm. Figure 2 As shown, the prepared MoO2@MoS2@C material inherits the nanorod morphology of the MoO3 template. The width of the nanorod is about 300nm and the length is about 2μm. Many nanocarbon particles derived from polypyrrole grow on its surface.
[0065] Figure 3 This is a diagram showing the element surface distribution results of the molybdenum-based negative electrode material prepared in Example 1. Figure 3 As shown, the five elements C, N, S, Mo, and O are evenly distributed in the prepared MoO2@MoS2@C material, indicating that the surface carbon coating formed after carbonization of polypyrrole and ammonium persulfate has the co-doping characteristics of nitrogen and sulfur.
[0066] Figure 4Figure a) is the X-ray diffraction pattern of the molybdenum-based negative electrode material prepared in Example 1. In the prepared MoO2@MoS2@C material, two active ingredients, MoS2 and MoO2, were successfully formed, both of which have good crystallinity; MoS2 showed significant diffraction peaks at 14.3°, 33.0° and 58.6°, corresponding to the (002), (100) and (110) crystal planes of the 2H phase, respectively; MoO2 showed significant diffraction peaks at 26.2°, 37.1° and 53.7°, corresponding to the (110), (200) and (220) crystal planes of the monoclinic phase MoO2, respectively.
[0067] The prepared MoO2@MoS2@C was used as the negative electrode material, polyvinylidene fluoride was used as the binder, and N-methyl-2-pyrrolidone was used as the solvent to prepare a uniform slurry, in which the mass ratio of the negative electrode material to the binder was 9:1. The slurry was applied on a clean copper foil and then dried at 120°C under vacuum conditions for 12 hours. The copper foil loaded with the slurry was cut into round electrode sheets with a diameter of 12 mm and compacted. When assembling the sodium ion battery, a metal sodium sheet and a glass fiber membrane (Whatman, GF-D) were used as the positive electrode and the diaphragm, respectively. The electrolyte was 1 mol / L NaClO4 (mixed solvent: ethylene carbonate / diethyl carbonate / fluoroethylene carbonate, volume ratio of 1:1:0.1), and the round electrode sheet was the negative electrode. It was assembled into a CR2032 button half-cell in an argon-filled glove box and stood for 8 hours at 0.1~3.0V (vs.Na + / Na) to test the charge and discharge performance. When assembling lithium-ion batteries, polypropylene film was used as the diaphragm, and the electrolyte was 1 mol / L LiPF6 (mixed solvent: dimethyl carbonate / ethylene carbonate / ethyl methyl carbonate, volume ratio of 1:1:1). CR2032 button half-cells were assembled in an argon-filled glove box. After standing for 8 hours, the battery was tested at 0.1-3.0V (vs.Li + / Li) to test the charge and discharge performance.
[0068] Fig.10 Figure a) shows the charge and discharge curve of the molybdenum-based negative electrode material prepared in Example 1. When the prepared MoO2@MoS2@C material is used in a sodium ion battery, the first cycle discharge specific capacity at a current density of 0.1A / g is as high as 649.1mAh / g, which is equivalent to the theoretical specific capacity of MoS2. The discharge specific capacity after cycle stabilization is about 393.3mAh / g.
[0069] Fig.11Figure a) is a rate performance diagram of the molybdenum-based negative electrode material prepared in Example 1. When the prepared MoO2@MoS2@C material is used in sodium ion batteries, the specific capacities at current densities of 0.1, 0.2, 0.5, 1.0, 2.0, and 5.0 A / g are 393.5, 327.8, 304.8, 276.5, 252.2, and 219.5 mAh / g, respectively, indicating that the material has excellent rate performance.
[0070] Fig.12 a) is the cycle stability performance of the molybdenum-based negative electrode material prepared in Example 1 when used in a sodium ion battery under a current density of 0.1 A / g. When the prepared MoO2@MoS2@C material is used in a sodium ion battery, it can be stably cycled for up to 160 cycles at a current density of 0.1 A / g, and can be stably cycled for up to 350 cycles at a current density of 1.0 A / g, indicating that the material has very high sodium ion battery cycle stability at low rates.
[0071] Fig.13 a) is the cycle stability performance of the molybdenum-based negative electrode material prepared in Example 1 when used in a sodium ion battery under a current density of 1.0 A / g. When the prepared MoO2@MoS2@C material is used in a sodium ion battery, it can be stably cycled for up to 350 cycles at a current density of 1.0 A / g, indicating that the material has very high sodium ion battery cycle stability at a higher rate.
[0072] Fig.14 The molybdenum-based negative electrode material prepared in Example 1 has a cycle stability performance at a current density of 5.0 A / g when used in a sodium ion battery. Fig.14 As shown, when the prepared MoO2@MoS2@C material is used in sodium ion batteries, it can be stably cycled for up to 1000 cycles at a current density of 5.0A / g, indicating that the material still has very high sodium ion battery cycle stability at high rates.
[0073] Fig.15 Figure a) shows the charge and discharge curve of the molybdenum-based negative electrode material prepared in Example 1 when used in a lithium-ion battery, and figure b) shows the rate performance. The prepared MoO2@MoS2@C material has a very high specific capacity. The first-cycle discharge specific capacity at a current density of 0.1A / g is as high as 890.0mAh / g, far exceeding the theoretical specific capacity of MoS2 and MoO2. The discharge specific capacity after cycle stabilization is about 646.3mAh / g, and a significant charge and discharge platform appears; the specific capacities at current densities of 0.1, 0.2, 0.5, and 1.0A / g are 634.9, 595.4, 542.4, and 491.8mAh / g, respectively, indicating that the material has excellent rate performance.
[0074] Fig.16The molybdenum-based negative electrode material prepared in Example 1 has a cycle stability performance at a current density of 0.2 A / g when used in a lithium-ion battery. Fig.15 As shown, when the prepared MoO2@MoS2@C material is used in lithium-ion batteries, it can be stably cycled for up to 300 cycles at a current density of 0.2A / g, indicating that the material has very high lithium-ion battery cycle stability.
[0075] Embodiment 2~5:
[0076] The preparation methods of Examples 2 to 5 are the same as those of Example 1, except for the amount of pyrrole monomer solution added, the concentration of ammonium persulfate solution, and the temperature of high-temperature pyrolysis. The specific reaction parameters are listed in Table 1. The molybdenum-based materials prepared in Examples 2 to 5 were used as negative electrode materials, polyvinylidene fluoride was used as a binder, and N-methyl-2-pyrrolidone was used as a solvent to prepare a uniform slurry, wherein the mass ratio of the negative electrode material to the binder was 9:1. The slurry was coated on a clean copper foil and then dried at 120°C under vacuum for 12 hours. The copper foil loaded with the slurry was cut into round electrode sheets with a diameter of 12 mm and compacted. When assembling the sodium ion battery, a sodium metal sheet and a glass fiber membrane (Whatman, GF-D) were used as the positive electrode and the separator, respectively. The electrolyte was 1 mol / L NaClO4 (mixed solvent: ethylene carbonate / diethyl carbonate / fluoroethylene carbonate, volume ratio of 1:1:0.1). The round electrode sheet was used as the negative electrode. The battery was assembled into a CR2032 button half-cell in an argon-filled glove box. After standing for 8 hours, the battery showed a positive voltage of 0.1-3.0 V (vs. Na + / Na) to test the charge and discharge performance, the results are shown in Table 1.
[0077] Table 1 Reaction parameters and battery performance results of Examples 2 to 5
[0078]
[0079]
[0080] Comparative Example 1: 0.618 g of ammonium molybdate tetrahydrate (Mo content is 3.5 mmol) and 0.014 g of ferric chloride hexahydrate (Fe content is 0.005 mmol) were weighed and added into 20 mL of a continuously stirred 0.25 mol / L dilute nitric acid solution in sequence, and a clear and transparent mixed solution was obtained after complete dissolution. The mixed solution was then transferred into a 40 mL polytetrafluoroethylene-lined reactor and placed in a 200 ° C oven for constant temperature reaction for 20 hours. After the hydrothermal reaction was completed, the MoO3 nanorods were separated by centrifugation, washed with water and ethanol in sequence for purification, and dried to collect;
[0081] 0.144 g MoO3 nanorods (1.0 mmol) were ultrasonically dispersed in 40 mL deionized water. Under ice bath and continuous stirring conditions, 675 μL pyrrole monomer solution (10.0 mmol) was injected. Then 10 mL of 1.0 mol / L ammonium persulfate solution (S content was 10.0 mmol) treated in an ice bath was added dropwise to initiate the polymerization reaction of the pyrrole monomer. It was observed that the mixed solution quickly changed from white to black. The ice bath and stirring reaction were continued for 5 hours. The ammonium persulfate initiator was removed by centrifugation and purification. After sufficient drying, a molybdenum trioxide-polypyrrole precursor was obtained.
[0082] The molybdenum trioxide-polypyrrole precursor was placed in a quartz boat and loaded into a programmed temperature tubular furnace. Argon gas was introduced at a flow rate of 30 mL / min for protection. The temperature was first increased from room temperature to 300°C at a rate of 1°C / min and maintained for 3 hours. Then the temperature was continued to be increased to 700°C at a rate of 10°C / min and maintained for 2 hours for confined pyrolysis treatment. After the furnace body was naturally cooled to room temperature, a nitrogen-doped carbon-coated molybdenum dioxide negative electrode material (named MoO2@C) was obtained.
[0083] Figure 4 Figure b) is the X-ray diffraction pattern of MoO2@C prepared in Comparative Example 1. The prepared MoO2@C material showed significant diffraction peaks at 26.2°, 37.1° and 53.7°, corresponding to the (110), (200) and (220) crystal planes of monoclinic MoO2, respectively. The 2H phase MoS2 formed in Example 1 was not detected.
[0084] Figure 5 Figure a) is a transmission electron microscope image of MoO2@C prepared in Comparative Example 1. The prepared MoO2@C material has a nanorod-like morphology with a width of about 300 nm. Its surface is coated with a carbon layer and the interior is highly crystalline MoO2. Figure b) is a selected area electron diffraction image in which clear diffraction spots can be observed on its (110) and (200) crystal planes.
[0085] The prepared nitrogen-doped carbon-coated molybdenum dioxide negative electrode material was mixed and dispersed with PVDF binder and NMP solvent to form a uniform slurry, in which the mass ratio of the negative electrode material to the binder was 9:1. The slurry was coated on a clean copper foil and then dried at 120°C under vacuum for 12 hours. The copper foil loaded with the slurry was cut into round electrode sheets with a diameter of 12 mm and compacted. When assembling the sodium ion battery, a metal sodium sheet and a glass fiber membrane (Whatman, GF-D) were used as the positive electrode and the diaphragm, respectively. The electrolyte was 1 mol / L NaClO4 (mixed solvent: ethylene carbonate / diethyl carbonate / fluoroethylene carbonate, volume ratio of 1:1:0.1), and the round electrode sheet was the negative electrode. It was assembled into a CR2032 button half-cell in an argon-filled glove box and stood for 8 hours at 0.1~3.0V (vs.Na + / Na) to test the charge and discharge performance.
[0086] Fig.10 Figure b) is the charge and discharge curve of MoO2@C prepared in Comparative Example 1. When the MoO2@C material prepared in Comparative Example 1 is used in a sodium ion battery, the first cycle discharge capacity at a current density of 0.1 A / g is 538.3 mAh / g, and the discharge capacity after cycle stabilization is about 320.2 mAh / g, which is much lower than the MoO2@MoS2@C material prepared in Example 1.
[0087] Fig.11 Figure b) is a rate performance diagram of MoO2@C prepared in Comparative Example 1. When the MoO2@C material prepared in Comparative Example 1 is used in sodium ion batteries, the specific capacities at current densities of 0.1, 0.2, 0.5, 1.0, 2.0, and 5.0 A / g are 300.2, 256.2, 240.1, 223.8, 200.8, and 170.7 mAh / g, respectively. The specific capacity at any current density is much lower than that of the MoO2@MoS2@C material prepared in Example 1, indicating that the construction of core-shell MoO2-MoS2 heterogeneous materials helps to accelerate the electrochemical reaction kinetics and improve the rate performance of sodium ion batteries.
[0088] Fig.12 Figure b) shows the cycle stability performance of the MoO2@C material prepared in Comparative Example 1 when used in sodium ion batteries under a current density of 0.1 A / g. The specific capacity decays sharply after 140 cycles, indicating that the core-shell MoO2-MoS2 heterogeneous material gives the MoO2@MoS2@C material prepared in Example 1 high cycle stability at low rates in sodium ion batteries.
[0089] Fig.13Figure b) shows the cycle stability performance of the MoO2@C material prepared in Comparative Example 1 when used in sodium ion batteries under a current density of 1.0 A / g. Its cycle stability is far inferior to that of the MoO2@MoS2@C material prepared in Example 1, indicating that the core-shell MoO2-MoS2 heterogeneous material also gives the MoO2@MoS2@C material prepared in Example 1 high cycle stability at higher rates in sodium ion batteries.
[0090] Comparative Example 2
[0091] 0.618 g of ammonium molybdate tetrahydrate (Mo content is 3.5 mmol) and 0.014 g of ferric chloride hexahydrate (Fe content is 0.005 mmol) were weighed and added in sequence to 20 mL of a continuously stirred dilute nitric acid solution with a concentration of 0.25 mol / L. After complete dissolution, a clear and transparent mixed solution was obtained. The solution was then transferred to a 40 mL polytetrafluoroethylene-lined reactor and placed in a 200 °C oven for constant temperature reaction for 20 hours. After the hydrothermal reaction was completed, the MoO3 nanorods were separated by centrifugation, washed with water and ethanol in sequence for purification, and collected after drying.
[0092] 0.144 g MoO3 nanorods (1.0 mmol) were ultrasonically dispersed in 40 mL deionized water. Under ice bath and continuous stirring conditions, 675 μL pyrrole monomer solution (10.0 mmol) was injected. Then 10 mL of 1.0 mol / L ice-bath treated ammonium persulfate solution (S content was 10.0 mmol) was added dropwise to initiate the polymerization reaction of the pyrrole monomer. It was observed that the mixed solution quickly changed from white to black. The ice bath and stirring reaction were continued for 5 hours. The ammonium persulfate initiator was removed by centrifugation and purification. After sufficient drying, a molybdenum trioxide-polypyrrole precursor was obtained.
[0093] The molybdenum trioxide-polypyrrole precursor and 320 mg of sulfur powder (S content is 10.0 mmol) are ground evenly and placed in a quartz boat, loaded into a programmed temperature tubular furnace, and argon gas is introduced at a flow rate of 30 mL / min for protection. The temperature is first increased from room temperature to 300°C at a rate of 1°C / min and maintained for 3 hours. Then the temperature is continued to be increased to 700°C at a rate of 10°C / min and maintained for 2 hours for confined pyrolysis treatment. After the furnace body is naturally cooled to room temperature, nitrogen and sulfur co-doped carbon-coated molybdenum dioxide-molybdenum disulfide composite negative electrode material (named MoO2 / MoS2@C-1) is obtained.
[0094] Figure 4c) is the X-ray diffraction pattern of MoO2 / MoS2@C-1 prepared in Comparative Example 2. In the prepared MoO2 / MoS2@C-1 material, two active components, MoS2 and MoO2, are formed, both of which have good crystallinity; MoS2 shows significant diffraction peaks at 14.3°, 33.0° and 58.6°, corresponding to the (002), (100) and (110) crystal planes of the 2H phase, respectively; MoO2 shows significant diffraction peaks at 26.2°, 37.1° and 53.7°, corresponding to the (110), (200) and (220) crystal planes of the monoclinic phase MoO2, respectively; compared with the MoO2@MoS2@C material prepared in Example 1, the MoS2 content in MoO2 / MoS2@C-1 is greatly increased.
[0095] Figure 6 Scanning electron microscope images of the MoO2 / MoS2@C-1 material prepared in Comparative Example 2 at different magnifications show that although the prepared MoO2 / MoS2@C-1 material exhibits a nanorod-like morphology similar to that of Example 1, with many nanocarbon particles derived from polypyrrole grown on the surface, some nanosheets are also formed and scattered on the surface.
[0096] Figure 7 The transmission electron micrographs of the MoO2 / MoS2@C-1 material prepared in comparative example 2 at different magnifications show that the core-shell MoO2-MoS2 nanoscrolls of Example 1 are not formed in the prepared MoO2 / MoS2@C-1 material. Instead, many clear (002) interlayer spacing lattice fringes of 2H phase MoS2 are observed on the surface of the nanorods, indicating that the additionally added sulfur powder as a sulfur source cannot form core-shell MoO2-MoS2 nanoscrolls.
[0097] The prepared nitrogen and sulfur co-doped carbon-coated molybdenum dioxide-molybdenum disulfide composite negative electrode material was mixed and dispersed with PVDF binder and NMP solvent to prepare a uniform slurry, in which the mass ratio of negative electrode material to binder was 9:1. The slurry was coated on a clean copper foil and then dried at 120°C under vacuum for 12 hours. The copper foil loaded with the slurry was cut into round electrode sheets with a diameter of 12 mm and compacted. When assembling the sodium ion battery, a metal sodium sheet and a glass fiber membrane (Whatman, GF-D) were used as the positive electrode and the diaphragm, respectively. The electrolyte was 1 mol / L NaClO4 (mixed solvent: ethylene carbonate / diethyl carbonate / fluoroethylene carbonate, volume ratio of 1:1:0.1), and the round electrode sheet was the negative electrode. It was assembled into a CR2032 button half-cell in an argon-filled glove box and stood for 8 hours at 0.1~3.0V (vs.Na + / Na) to test the charge and discharge performance.
[0098] Fig.11Figure c) is a rate performance diagram of MoO2 / MoS2@C-1 prepared in Comparative Example 2. When the MoO2 / MoS2@C-1 material prepared in Comparative Example 2 is used in a sodium ion battery, the specific capacities at current densities of 0.1, 0.2, 0.5, 1.0, 2.0, and 5.0 A / g are 236.8, 210.5, 189.9, 169.6, 149.2, and 128.4 mAh / g, respectively. The specific capacity at any current density is much lower than that of the MoO2@MoS2@C material prepared in Example 1, and also lower than that of the MoO2@C material prepared in Comparative Example 1.
[0099] Comparative Example 3
[0100] The preparation method of Comparative Example 3 is the same as that of Comparative Example 2, except that 320 mg of sulfur is replaced with 761 mg of thiourea (S content is 10.0 mmol) and ground evenly with the molybdenum trioxide-polypyrrole precursor, and then subjected to high-temperature pyrolysis to obtain a nitrogen and sulfur co-loaded carbon-molybdenum dioxide-molybdenum disulfide composite negative electrode material (named MoO2 / MoS2@C-2).
[0101] Figure 4 Figure d) is the X-ray diffraction pattern of MoO2 / MoS2@C-2 prepared in Comparative Example 3. In the prepared MoO2 / MoS2@C-2 material, 2H phase MoS2 has significant diffraction peaks at 14.3°, 33.0° and 58.6°, corresponding to the (002), (100) and (110) crystal planes, respectively, while MoO2 has only weak diffraction peaks at 26.2°, 37.1° and 53.7°, corresponding to the single crystal planes. The (110), (200) and (220) crystal planes of the oblique phase MoO2 indicate that compared with the MoO2@MoS2@C material prepared in Example 1 and the MoO2 / MoS2@C-1 material prepared in Comparative Example 2, the MoS2 content in MoO2 / MoS2@C-2 is further increased, that is, the sulfur source is changed from the strongly oxidizing ammonium persulfate to sulfur powder, and then to the reducing thiourea. The content of 2H phase MoS2 formed during the pyrolysis process will gradually increase significantly.
[0102] Figure 8 The scanning electron microscope images of the MoO2 / MoS2@C-2 material prepared in comparative example 3 at different magnifications show that the prepared MoO2 / MoS2@C-2 material no longer has the nanorod-like morphology similar to that in example 1, and many nanosheets stacked on each other are formed on the surface.
[0103] Fig. 9The transmission electron micrographs of the MoO2 / MoS2@C-2 material prepared in comparative example 3 at different magnifications show that the core-shell MoO2-MoS2 nanoscrolls of Example 1 are not formed in the prepared MoO2 / MoS2@C-2 material. Instead, a large number of clear (002) interlayer lattice fringes of 2H phase MoS2 are observed on the carbon support, indicating that the additionally added thiourea as a sulfur source cannot form core-shell MoO2-MoS2 nanoscrolls.
[0104] Fig.11 d) is the rate performance diagram of MoO2 / MoS2@C-2 prepared in Comparative Example 3. When the MoO2 / MoS2@C-2 material prepared in Comparative Example 3 is used in a sodium ion battery, the specific capacities at current densities of 0.1, 0.2, 0.5, 1.0, 2.0, and 5.0 A / g are 205.8, 178.5, 154.8, 135.7, 106.3, and 82.4 mAh / g, respectively. The specific capacity at any current density is much lower than that of the MoO2@MoS2@C material prepared in Example 1, and also much lower than that of the MoO2 / MoS2@C-1 material prepared in Comparative Example 2.
[0105] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0106] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A molybdenum-based negative electrode material, characterized in that: The invention comprises a carbon nanorod co-doped with nitrogen and sulfur, wherein the carbon nanorod is filled with a core-shell molybdenum-based nanoscroll; The core-shell molybdenum-based nanoscroll comprises a molybdenum dioxide core and a molybdenum disulfide shell layer with a curved structure, and the number of layers of the molybdenum disulfide is 12 to 35.
2. The method for preparing a molybdenum-based negative electrode material according to claim 1, characterized in that: include: The molybdenum trioxide nanorods are dispersed in water, and a nitrogen-containing organic carbon source monomer solution is injected under ice bath conditions, and a sulfur-containing initiator with strong oxidizing properties is used to initiate the reaction, and after the reaction, a molybdenum trioxide-organic polymer precursor dispersed with the sulfur-containing initiator is obtained; Under the protection of an inert atmosphere, the molybdenum trioxide-organic polymer precursor dispersed with the sulfur-containing initiator is subjected to confined pyrolysis at 600-800° C. to obtain the molybdenum-based negative electrode material; wherein the molar ratio of the molybdenum trioxide nanorods, the nitrogen-containing organic carbon source monomer and the sulfur-containing initiator is 1.0:5-15:1.
0.
3. The method for preparing a molybdenum-based negative electrode material according to claim 2, characterized in that: During the confined pyrolysis, the temperature is first raised from room temperature to 300° C. at a rate of 1° C. / min for 3 hours, and then the temperature is further raised to 600-800° C. at a rate of 2-10° C. / min for 2-5 hours.
4. The method for preparing a molybdenum-based negative electrode material according to claim 2, characterized in that: The sulfur-containing initiator is ammonium persulfate.
5. The method for preparing a molybdenum-based negative electrode material according to claim 4, characterized in that: When preparing the molybdenum trioxide-organic polymer precursor dispersed with a sulfur-containing initiator, the ammonium persulfate is first prepared into a solution and then the reaction is initiated; wherein the concentration of the ammonium persulfate solution is 1.0-3.0 mol / L.
6. The method for preparing a molybdenum-based negative electrode material according to claim 2, characterized in that: The nitrogen-containing organic carbon source monomer is one or more of pyrrole, aniline and dopamine hydrochloride.
7. The method for preparing a molybdenum-based negative electrode material according to claim 2, characterized in that: The preparation method of the molybdenum trioxide nanorods is: Molybdate and ferric chloride hexahydrate are added into a nitric acid solution and subjected to a constant temperature hydrothermal reaction to obtain molybdenum trioxide nanorods.
8. The method for preparing a molybdenum-based negative electrode material according to claim 7, characterized in that: The molar ratio of molybdenum in the molybdate, iron in ferric chloride hexahydrate, and nitric acid is 0.5-4.0:0.01-0.05:1.0-5.
0.
9. The method for preparing a molybdenum-based negative electrode material according to claim 7, characterized in that: The constant temperature hydrothermal reaction is carried out at 150-220° C. for 15-25 hours.
10. Use of the molybdenum-based negative electrode material according to claim 1 in a negative electrode of a sodium ion battery or a negative electrode of a lithium ion battery.
Citation Information
Patent Citations
MoO2-MoS2 negative electrode material of sodium-ion battery with core-shell structure and preparation method of MoO2-MoS2 negative electrode material
CN106410150A
Preparation method of Molybdenum Disulfide / Nitrogen Doped Carbon Nanowire negative electrode Material
CN109065867A
High-performance electrochemical capacitor negative electrode material molybdenum dioxide and nitrogen-doped carbon composite material and preparation method and application thereof
CN110364366A
Molybdenum-based core-shell structure material and preparation method and application thereof
CN114613969A
Carbon material for nonaqueous electrolyte battery, electrode for nonaqueous electrolyte battery using the same, and nonaqueous electrolyte battery
JP2004342463A
Cited By
Micro-mesoporous nitrogen-sulfur double-doped hard carbon as well as preparation method and application thereof
CN120864473A